About agricultural manuals, gardens and coffee plantations: mosaics and landscape transformation in the Paraiba do Sul Valley, Brazil - Santa Cruz de Assis Brasil, Lucas; Oliveira, Rogério Ribeiro de (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2020)
Economic cycles have often become the landscape matrix, in a hybrid process of society-nature transformation, leaving distinct legacies in it. The coffee plantation showed great productivity in the Paraíba do Sul Valley to the detriment of forests, resulting in profound changes in geo-hydric cycles. Although the transformation by coffee has been significant on a spatial scale and in environmental changes, the Paraíba do Sul Valley landscape needs to be understood in a broader perspective. There were also other crops in the landscape inside or outside large estates. This work aims to recognize the spatial organization of these cultures and develop an understanding of the pattern of the coffee landscape, showing the performance of different social actors. The methodology consisted of a bibliographic review and analysis of historical agricultural manuals. Spatializing such past activities and social groups in the landscape shows us what was previously hidden, omitted by the traditional historical narrative This research showed that colonial knowledge developed a landscape compartmentalization, spatializing the crops according to pedological and topographic evidence.